Language shift in Aceh: The sociolinguistic situation of post-conflict society - Teuku Muhammad Ridha Al-Auwal; Robert Amery; Ian Green (Studies in English Language and Education)
Aceh is a special autonomous province of Indonesia located on the northwest tip of Sumatra Island. Aceh had been in conflict with the Indonesian government for more than 3 decades before officially declaring peace in 2005. This study aims to shed light on the sociolinguistic situation in Aceh during the conflict and following the 2005 peace accord, as well as to provide a deeper understanding of the roots of Aceh’s rapid language shift. Based on focus groups with young people and young parents, as well as follow-up interviews with members of an earlier generation, the study revealed that the prolonged conflict between Aceh and Indonesia failed to lead to resistance. Instead of being a colonial language, Indonesian is an integral part of national identity. Even though there was still a stated pride and high level of ideological identification with Acehnese, a gradual shift away from Acehnese began during the conflict. Since the 1970s and 1980s, an emerging phenomenon of Indonesian intergenerational transmission has emerged. This linguistic phenomenon then became more and more common among Acehnese families in the 2000s and peaked after the tsunami and peace agreement. Prestige/modernity, education, and socioeconomic factors seem to be the primary drivers of the Acehnese-to-Indonesian language shift.